The Relationship Between Temperature, Greenhouse Gas Emissions, and Malaria Cases in Indonesia: Original Article - Fairuz Haniyah Ramadhani; Azizah R.; Mir Atudz Dzikro (Journal of Diverse Medical Research : Medicosphere, 2026)
Malaria is still a public health problem in Indonesia and had the potential to be affected by climate change due to greenhouse gas emissions. This study aimed to analyze the correlations among greenhouse gas emissions across sectors, temperature, humidity, and malaria incidence in Indonesia. The study used an ecological design with a quantitative observational approach based on national aggregate data for the period 2000–2019. Greenhouse gas emission data were obtained from national inventory reports, temperature and humidity data from BMKG, and malaria data from BPS. Statistical analysis was carried out using the Spearman rank correlation test. The results showed that only the emissions of the Industrial Processes and Product Use (IPPU) sector had a strong and significant positive correlation with temperature (p = 0.025). In contrast, the other emission sectors were not significant. In addition, temperature and humidity showed a strong, significant negative correlation with malaria incidence (p = 0.007 and p = 0.005). These findings confirm that the relationship between climate and malaria is complex and non-linear, and is influenced by non-climatic factors such as strengthening of health systems and vector control.